Iowa Birdline update, January 28, 1991 notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Notes for the Iowa Birdline update for January 28, 1991. Highlights include reports from a long weekend foray a group of Iowa birders took in eastern Iowa. Epson - sheet feed/flatbed